Single-axis combined shearography and digital speckle photography instrument for full surface strain characterization - Groves, Roger M.; Fu, S.; James, Stephen W.; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2005)
Full characterization of the surface strain requires the measurement of six displacement gradient components of the surface strain tensor. The out-of-plane displacement gradient component may be directly measured using the full-field speckle interferometry technique of shearography, but to fully characterize the surface strain using shearography, a minimum of three illumination, or viewing, directions are required. The image processing technique of digital speckle photography (DSP) is sensitive to in-plane displacement for normal collinear illumination and viewing, with the displacement gradient components obtained by differentiation. A combination of shearography and digital speckle photography is used to perform full characterization of the surface strain using a single illumination and viewing direction. The increase in complexity compared with a standard single-channel shearography system lies predominantly in the additional image processing requirements. Digital speckle photography image processing is performed using the optical flow field technique and the advantages of this technique compared with correlation are discussed. The design of the instrument is described and full surface strain measurements made with the system are presented.
Keywords: strain measurement limited optical access shearography digital speckle photography field-measurements image-correlation displacement interferometry algorithm